Tumor grafted – chick chorioallantoic membrane as an alternative model for biological cancer research and conventional/nanomaterial-based theranostics evaluation. (3rd August 2021) - Mapanao, Ana Katrina; Che, Pei Pei; Sarogni, Patrizia; Sminia, Peter; Giovannetti, Elisa; Voliani, Valerio
ABSTRACT: Introduction : Advancements in cancer management and treatment are associated with strong preclinical research data, in which reliable cancer models are demanded. Indeed, inconsistent preclinical findings and stringent regulations following the 3Rs principle of reduction, refinement, and replacement of conventional animal models currently pose challenges in the development and translation of efficient technologies. The chick embryo chorioallantoic membrane (CAM) is a system for the evaluation of treatment effects on the vasculature, therefore suitable for studies on angiogenesis. Apart from vascular effects, the model is now increasingly employed as a preclinical cancer model following tumor-grafting procedures. Areas covered : The broad application of CAM tumor model is highlighted along with the methods for analyzing the neoplasm and vascular system. The presented and cited investigations focus on cancer biology and treatment, encompassing both conventional and emerging nanomaterial-based modalities. Expert opinion : The CAM tumor model finds increased significance given the influences of angiogenesis and the tumor microenvironment in cancer behavior, then providing a qualified miniature system for oncological research. Ultimately, the establishment and increased employment of such a model may resolve some of the limitations present in the standard preclinical tumor models, thereby redefining the preclinical research workflow.